Understanding historical change and the multiperspective through comics: a study with Portuguese students on the subject of feminism - Solé, Glória; Santos, Inês (Clio. History and History Teaching, 2023)
This article aims to present a pedagogical intervention and research study with Portuguese 9th grade students (14-15 years old) from a school in the North of Portugal. The aim of this study was to understand what historical value students attribute to historical comics, as well as to know if they can, through it, build historical knowledge subordinated to the theme of feminism, in which we also sought to work on the concepts of historical change and multiperspective. The data were obtained from individual tasks, questionnaires of previous ideas/metacognition and a worksheet, which were analysed according to a more comprehensive methodological approach called Grounded Theory. We concluded that most students understood the changes that occurred under this theme, however, they could not easily identify how they happened, or at what speed. With regard to comics, this study showed that students value this resource to work with history and more easily understand historical changes.